Genetic diversity of avian influenza virus strains A/H3N8 (Experimental biology, 2020)
The spread of influenza A viruses (IAV) in nature is inextricably linked to migratory movements of wild birds, which is a natural reservoir of avian influenza virus in nature. The paper presents monitoring data on the territory of the Republic of Kazakhstan in 2018 -2019, during which the IAV/H3N8 circulation was detected among the wild bird population. Changes in the genetic structure of surface genes circulating on the territory of Kazakhstan of five IAV/H3N8 strains were analyzed and their phylogenetic affiliation was determined. The genetic distances of the IAV/H3N8 surface genes identified using the MEGA software version 6.0 show that Kazakhstani strains distance themselves from the Asian and European IAV/H3N8 strains and form a separate branch that differs from the prototype strains. Perhaps these Kazakhstani strains are new variants of IAV/H3N8. Five Kazakhstan HAV / H3N8 strains and strains of the Eurasian genetic branch also demonstrated phylogenetic closeness in the nucleotide sequences of neuraminidase. Moreover, the genetic distance between the Kazakhstani strains of the HAV / H3N8 and the closest Asian strain A / duck / Mongolia / 566/2018 (H3N8) MK978954 was D≥0.015. Kazakhstani strains distance themselves from European strains like A / mallard / Sweden / 141811/2013 (H3N8) KT725427 with a value of D ≥0.027.
Keywords: influenza virus, strain, genetic diversity